Bioconversion of Organic Residues into Single Cell Protein (SCP): Turning Debris into Delicacies - Aloo , Nancy Becky; Matasyoh , Lexa Gomezgani; Too , Emily Jepkosgei (African Journal of Education,Science and Technology (AJEST), 2013)
The increasing world deficiency of protein is becoming a major problem for mankin d. The conventional sources of protein are scarce and costly and since the early fifties, intense efforts have been made to explore new, alternative and unconventional sources of protein. For this reason, fungi, bacteria and algae have been explored as alternative sources of protein broadly known as single cell protein (SCP). SCP has a number of advantages when used as food or feed ; the most important of which is the high protein content (30-80 %) in the cells. Furthermore, SCP also contains fats, carbohydrates, nucleic acids, vitamins and minerals all of which are important dietary components in feeds and food. SCP products are also rich in certain essential amino acids such as lysine and methionine which are usually limiting in most plant and animal foods. Thus, SCP is of high nutritional value for human and/or animal consumption and since SCP production can be done on agricultural and other organic wastes, the utilization of these wastes in SCP production serves two functions; reduction of pollution or environmental conservation and the creation of edible protein. The main aim of this work was to review the use of organic wastes in production of edible protein and to provide highlights on the novelty of SCP.